2021
DOI: 10.3390/biom11020180
|View full text |Cite
|
Sign up to set email alerts
|

BanLec-eGFP Chimera as a Tool for Evaluation of Lectin Binding to High-Mannose Glycans on Microorganisms

Abstract: Fluorescently labeled lectins are useful tools for in vivo and in vitro studies of the structure and function of tissues and various pathogens such as viruses, bacteria, and fungi. For the evaluation of high-mannose glycans present on various glycoproteins, a three-dimensional (3D) model of the chimera was designed from the crystal structures of recombinant banana lectin (BanLec, Protein Data Bank entry (PDB): 5EXG) and an enhanced green fluorescent protein (eGFP, PDB 4EUL) by applying molecular modeling and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…More recently, computer modeling showed that H84T BanLec is expected to bind the SARS-CoV-2 S-glycoprotein with high affinity 23 . Wild-type BanLec is active against additional pathogens, including bovine viral diarrheal virus (BVDV) and bovine alphaherpesvirus 1 (BoHV-1) 24 and Salmonella 25 . Interestingly, when a change similar to that which converted BanLec to H84T BanLec was made in the related Malaysian banana lectin, producing F84T Malay BanLec, broad-spectrum antiviral activity was retained and mitogenicity was reduced in a manner comparable to H84T BanLec 26 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, computer modeling showed that H84T BanLec is expected to bind the SARS-CoV-2 S-glycoprotein with high affinity 23 . Wild-type BanLec is active against additional pathogens, including bovine viral diarrheal virus (BVDV) and bovine alphaherpesvirus 1 (BoHV-1) 24 and Salmonella 25 . Interestingly, when a change similar to that which converted BanLec to H84T BanLec was made in the related Malaysian banana lectin, producing F84T Malay BanLec, broad-spectrum antiviral activity was retained and mitogenicity was reduced in a manner comparable to H84T BanLec 26 .…”
Section: Introductionmentioning
confidence: 99%
“…This BanLec-HIV recognition is thought to be mediated through mannose epitopes on high-mannose N-glycans [19]. BanLec is one of the most potent anti-viral lectins, but also recognizes bacteria with high-mannose type structures [19,20]. This makes BanLec very interesting as a very potent anti-infective agent with additional immune modulatory capacities [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…BanLec is one of the most potent anti-viral lectins, but also recognizes bacteria with high-mannose type structures [19,20]. This makes BanLec very interesting as a very potent anti-infective agent with additional immune modulatory capacities [20][21][22][23]. Further information about the intervention with the immune system is needed to understand respective processes.…”
Section: Introductionmentioning
confidence: 99%